PELATIHAN INTERNALISASI TOTAL QUALITY MANAGEMENT (TQM) DALAM PENJAMINAN MUTU LAYANAN PENDIDIKAN INKLUSIF DI SDN KALAPIAN KECAMATAN PONTANG KABUPATEN SERANG - Umalihayati Umalihayati; Erna Kusumawarti; Mutoharoh Mutoharoh; Ika Pratiwi; Uli Wildan; Islahiyah Islahiyah; Ramdan Ramdan; Eno Astriani; Astuti Astuti; Falih Ihza; Inti Hujah (Yayasan Education and Social Center, 2026)
This community service activity aimed to improve teachers’ understanding and competence in internalizing Total Quality Management (TQM) for quality assurance of inclusive education services at SDN Kalapian, Pontang District, Serang Regency. The activity was conducted in September 2025 involving principals, teachers, and educational staff through socialization, training, mentoring, and evaluation stages. The methods used included lectures, group discussions, simulations, and case studies related to inclusive education management and school quality culture. The results showed an increase in participants’ understanding of TQM concepts, inclusive education services, and school quality assurance systems. Participants also demonstrated stronger commitment and collaboration in developing sustainable quality culture within the school environment. In addition, the activity produced follow-up programs such as the establishment of a school quality assurance team, periodic evaluation of inclusive learning services, and continuous teacher competency development. The implementation of TQM in inclusive education services is expected to create adaptive, participatory, and sustainable educational quality improvement. Therefore, this activity contributes to strengthening the quality assurance system of inclusive elementary education and can serve as a model for similar schools in improving educational service quality.